Induction of sprouting in dormant yam (Dioscorea spp.) tubers with inhibitors of gibberellins - Shiwachi, H.; Ayankanmi, T.G.; Asiedu, Robert; Onjo, M. (Cambridge University Press, 2003)
A reliable means to induce sprouting in dormant seed tubers of yams (Dioscorea species) is required to enhance flexibility in planting date and rate of propagation of the crop. Experiments were conducted to assess the potential of two gibberellin inhibitors, Uniconazole-P and Prohexadione-calcium, to induce sprouting in tubers from three varieties of D. rotundata and four of D. alata. Uniconazole-P and Prohexadione-calcium shortened the period of dormancy in tubers of some varieties. In others, they either had no effect or extended dormancy. The varietal responses were also influenced by whether the tubers were treated at harvest (before shoot senescence) or four weeks after harvest by which time shoots had senesced fully. Tubers stored in darkness at a constant temperature of 30 °C sprouted earlier but lost weight faster than did those stored under natural daylight and ambient temperature. The apparent slow action of Uniconazole-P and Prohexadione-calcium, and their variable effectiveness in relation to variety, would limit their usefulness in seed or breeding programmes, or in determining treatment timing and the best storage environment for the tubers after treatment.